DISTANCE EDUCATION IN ARMENIA DURING COVID-19. DISCOURSE-ANALYSIS (EDUCATION IN THE 21ST CENTURY, 2023)
COVID-19 posed serious challenges to the education system, both globally and in individual countries, forcing a rapid transition from the traditional classroom to the online classroom. In Armenia 2020 after the establishment of the state of emergency due to the epidemic in March, the secondary schools switched to the format of online education. The study of this experience became relevant, aimed at revealing the problems encountered during online education and developing solutions to them.Numerous international studies have shown that the quality and accessibility of distance learning during the epidemic was directly affected by the availability of the Internet և technical resources, teacher skills և training on online learning tools.The aim of this article is to find out how students, parents, teachers, policy makers, education managers evaluate the education, the quality and effectiveness of distance education during the epidemic.Novelty. The quality and effectiveness of distance education in Armenia was assessed using the methodology of discourse analysis.
Keywords: Keywords: distance education, education quality, education policy, discourse analysis, education in Armenian during COVID-19.